2017
DOI: 10.1680/jmuen.16.00004
|View full text |Cite
|
Sign up to set email alerts
|

Briefing: Defining safety leadership in construction

Abstract: This briefing explores the tenets of safety leadership within the construction environment. The scope of this briefing aims to define a universal definition of safety leadership with key components from literature review. Without a clear definition towards safety leadership, a misalignment between safety expectations may occur which can create a misappropriation towards safety efforts. This may adversely impact injury rates within the workplace due to ill-conceived safety leadership behaviours. A detailed defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Many researchers proposed a variety of ways to improve of construction safety for the benefits of both the workers and organizations. Umar (2016-b) stressed on the universal definition of the safety leadership as he considered that in absence of a clear definition of safety leadership may result into the confusion in safety expectations and will disturb the safety efforts. Similarly, Umar and Wamuziri (2016-b) while exploring the challenges and opportunities for improvement of occupational safety and health in Oman, concluded that there is a need for establishing of an independent organizations responsible for the implementation of occupational safety and health regulations in Oman.…”
mentioning
confidence: 99%
“…Many researchers proposed a variety of ways to improve of construction safety for the benefits of both the workers and organizations. Umar (2016-b) stressed on the universal definition of the safety leadership as he considered that in absence of a clear definition of safety leadership may result into the confusion in safety expectations and will disturb the safety efforts. Similarly, Umar and Wamuziri (2016-b) while exploring the challenges and opportunities for improvement of occupational safety and health in Oman, concluded that there is a need for establishing of an independent organizations responsible for the implementation of occupational safety and health regulations in Oman.…”
mentioning
confidence: 99%
“…The first is a Briefing paper by Tariq Umar (2017), which reviews the literature to identify the key elements of safety leadership and offers a detailed definition of this as it applies to a construction environment. Its importance is emphasised, as a lack of clarity on what effective safety leadership looks like is seen to have a negative impact on rates of injury in the workplace.…”
mentioning
confidence: 99%